Analisis Perkembangan Usaha Warung Bakso Mas Tri Menggunakan Pendekatan Break Even Point (BEP) - Asifa Asifa; Zerent Gabriel Montoh; Priska Rahayaan; Selfita Brien; Imanuel Sasior; Josua Timoty; Paulinus Darmansi Ambang; Samuel Y.Warella (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2024)
This study aims to analyze the business development of mas tri meatball stalls using the Break Even Point (BEP) approach during January to February. The location of the tri mas meatball stall is located at Kilo meter 10 Sorong, Southwest Papua.The data analysis method used is quantitative descriptive analysis. The data collection technique used was a question and answer interview technique for meatball stall owners. The results of the research obtained are: The January 2024 Break Even Point is IDR 8,13,387,298. The February 2024 break even point is IDR 12,647,059. The results of this study show that profit planning has increased in February 2024.